Seeking Alternative of Trademark Cancellation in Indonesia: From Trademark Law to Religious Ethical Corporative Theory - Davinia, Sonya; Kansil, Christine S.T. (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2025)
Background: Trademark disputes in Indonesia often arise due to similarity in principle (persamaan pada pokoknya) and bad faith registration, as regulated under Law No. 20 of 2016 on Trademarks and Geographical Indications. However, Indonesia’s legal framework lacks clarity in protecting famous marks, preventing dilution, and ensuring procedural fairness in cancellation cases. A comparative analysis with Germany’s Markengesetz (Trademark Act) and an ethical assessment through Religious ethical Corporative Theory reveal critical gaps in Indonesia’s approach Purpose: This study aims to analyze the legal, economic, and ethical implications of trademark cancellation in Indonesia, comparing its framework with Germany’s trademark system while incorporating Islamic corporate responsibility principles Methods: The research employs normative legal analysis, integrating statutory interpretation, comparative legal research, and doctrinal analysis. Primary sources include Indonesian and German trademark laws, while secondary sources consist of journal articles, case law, and intellectual property treaties. The study also applies Religious ethical Corporative Theory to examine the moral and reputational consequences of bad faith trademark practices. Results: The study finds that Indonesia’s trademark cancellation system lacks procedural safeguards, particularly in protecting famous marks against dilution and bad faith registration. Unlike Germany’s Markengesetz, which establishes strict criteria for likelihood of confusion and dilution, Indonesia's legal provisions remain vague, leading to inconsistent enforcement and potential legal exploitation by multinational corporations. Additionally, from an Islamic corporate ethics perspective, bad faith trademark registration is not only a legal violation but also a breach of business accountability (Mas’uliyyah tijariyyah), warranting both legal and ethical remedies. Implication: This study provides three key contributions: (1) A comparative legal analysis demonstrating the need for stronger trademark protection mechanisms in Indonesia; (2) Integration of Islamic corporate ethics, highlighting moral accountability beyond legal compliance; and (3) Policy recommendations, urging Indonesia to adopt clearer evidentiary standards, align with international trademark regimes, and implement ethical accountability frameworks. By bridging legal, economic, and ethical perspectives, this study offers a novel framework for analyzing trademark disputes in emerging markets. Originality: Integration of Islamic corporate ethics, highlighting moral accountability beyond legal compliance